Efficacy and safety of hepatitis B vaccine: an umbrella review of meta-analyses - Jiamin Qiu; Shiwen Zhang; Yonghui Feng; Xin Su; Jun Cai; Shiyun Chen; Jiazi Liu; Shiqi Huang; Haokun Huang; Sui Zhu; Huiyan Wen; Jiaxin Li; et al. (Expert Review of Vaccines, 2024)
Background There is a lack of synthesis of literature to determine hepatitis B vaccine (HepB) strategies for hepatitis B virus (HBV) supported by quality evidence. We aimed to explore the efficacy and safety of HepB strategies among people with different characteristics.Research design and methods PubMed, Cochrane Library, Embase, and Web of Science were searched for meta-analyses comparing the efficacy and safety of HepB up to July 2023.Results Twenty-one meta-analyses comparing 83 associations were included, with 16 high quality, 4 moderate, and 1 low quality assessed by AMSTAR 2. Highly suggestive evidence supports HepB booster and HepB with 1018 adjuvant (HBsAg-1018) for improved seroprotection, and targeted and universal HepB vaccination reduced HBV infection Suggestive evidence indicated that targeted vaccination decreased the rate of hepatitis B surface antibody positivity and booster doses increased seroprotection in people aged 10–20. Weak evidence suggests potential local/systemic reaction risk with nucleotide analogs or HBsAg-1018. Convincing evidence shows HLA-DPB1*04:01 and DPB1*04:02 increased, while DPB1*05:01 decreased, hepatitis B antibody response. Obesity may reduce HepB seroprotection, as highly suggested.Conclusion Targeted vaccination could effectively reduce HBV infection, and adjuvant and booster vaccinations enhance seroprotection without significant reaction. Factors such as obesity and genetic polymorphisms may affect the efficacy.